PENGARUH CARA GURU MENGAJAR, PEMANFAATAN SARANA BELAJAR DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR IPS TERPADU - Kharisma Idola Arga (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
This study aims to determine whether there is influence the way teachers teach, the use of learning facilities and student learning motivation on the results of learning IPS Integrated students of class VII SMPN 1 Natar Lampung Selatan Lesson 2015/2016. The research method used in this research is descriptive verification with Ex Post Facto and Survey approach. The population in this study were all students of grade VII SMPN 1 Natar Lampung Selatan totaling 366 students with a sample size of 188 students, taken with random sampling sampling technique. Data collection techniques used were observation, documentation, interviews, and questionnaires. To test the hypotheses one, two, and three using a simple linear regression model and the fourth hypothesis using multiple regression models. Based on the data analysis, the research results show that: 1) .The influence of the way of teaching teacher to the learning result of IPS Integrated student of class VII SMPN 1 Natar Lampung Selatan Lesson Year 2015/2016. 2). There is influence of learning tool to study result of IPS Integrated student of class VII Accounting SMPN 1 Natar Lampung Selatan Lesson Year 2015/2016. 3). There is influence of student's learning motivation to result of study of IPS Integrated student of class VII SMPN 1 Natar Lampung Selatan Lesson Year 2015/2016. 3) .The influence of the way teachers teach, the use of learning facilities and student learning motivation on the learning outcomes IPS Integrated students class VII SMPN 1 Natar Lampung Selatan Lesson 2015/2016.